Democratic Values dan Toleransi Politik pada Mahasiswa Beragama Islam di Kota Makassar - Muh. Kasogi Nurdin (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2021)
Democracy is known as the greatest political system in the world, since it stresses collective compromise from all societal elements in developing the state. One of the democracyâ€™s results is political tolerance, which is the societyâ€™s tolerant-intolerant behavior towards minority group in socio-political activities. An individual acts tolerant on minority group with several factors, such as institutionalization, recognition, etc. In Indonesia context, majority group (Islam) is still acting intolerant towards most of the minority groups. Chinese-Indonesian ethnic community is one of the Indonesiaâ€™s minority groups, which has received discrimination from â€œNew Orderâ€ until â€œReformationâ€ period. This study aims to understand the effect of democratic values on political tolerance from Muslimsâ€™ university students in Makassar city, with Chinese-Indonesian ethnic community as the minority group which becomes the studyâ€™s object. The studyâ€™s method is quantitative, by using democratic valuesâ€™ measuring instrument from Saiful Mujani (2019), and political toleranceâ€™s measurement from Jeremy Menchik (2016). The result shows positive effect from democratic values on political tolerance, which presents Muslimsâ€™ university students in Makassar city to act tolerant on Chinese-Indonesian ethnic community.